2021
DOI: 10.1177/17470218211033118
|View full text |Cite
|
Sign up to set email alerts
|

Yes! I love my mother as much as myself: Self- and mother-association effects in an Indian sample

Abstract: Information associated with the self is preferentially processed compared to others. However, cultural differences appear to exist in the way information is processed about those close to us like our mothers. In eastern compared to western cultures, information about mother seems to be processed as well as our self. However, it is not clear whether this lack of difference is due to familiarity or would extend to processing arbitrary perceptual information associated with different categorical labels. The curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…A Friend-other advantage (in either RT, or accuracy/ d ′, or both) has emerged in some studies (Enock et al, 2018; Moseley et al, 2021; Stolte et al, 2017; Sui et al, 2012, 2013; Williams et al, 2018) but not others (Lee et al, 2021; Reuther & Chakravarthi, 2017). Previous research suggests that hierarchical relations between associations in the matching task may be altered across contexts; namely, by stimulus features (the frequency of tones paired with the identities; Stolte et al, 2021; or the combination of identities; A. Verma et al, 2021) or perhaps task difficulty in relation to the stimuli (Lee et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Friend-other advantage (in either RT, or accuracy/ d ′, or both) has emerged in some studies (Enock et al, 2018; Moseley et al, 2021; Stolte et al, 2017; Sui et al, 2012, 2013; Williams et al, 2018) but not others (Lee et al, 2021; Reuther & Chakravarthi, 2017). Previous research suggests that hierarchical relations between associations in the matching task may be altered across contexts; namely, by stimulus features (the frequency of tones paired with the identities; Stolte et al, 2021; or the combination of identities; A. Verma et al, 2021) or perhaps task difficulty in relation to the stimuli (Lee et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that hierarchical relations between associations in the matching task may be altered across contexts; namely, by stimulus features (the frequency of tones paired with the identities; Stolte et al, 2021; or the combination of identities; A. Verma et al, 2021) or perhaps task difficulty in relation to the stimuli (Lee et al, 2021). It may be that response features (arm movements rather than keypress responses) can also modulate these relations.…”
Section: Friend-stranger Biasmentioning
confidence: 99%
“…Interestingly, faster reaction time (RT) was reported in the self-associated shape-label matching condition compared to friend- and stranger-associated shape-label matching condition, showing a cognitive advantage for the newly learned self-associated geometric shapes over other associations (such as friend and stranger; Sui et al, 2012 ). Additionally, the cognitive benefit for self-associated shapes persisted even when participants made matching judgment on self and mother-associated pairs (Experiment 2 of Sui et al, 2012 ), suggesting that self-referential benefit is particular to the self and is not shared even with those close to self (such as mother; however see Verma et al, 2021 for cultural influences on mother-bias). This cognitive benefit for self is proposed to be driven by the heightened perceptual saliency of the self-associated items.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, self-advantage has been found only for the objects associated with the current self and not for the objects associated with the past and future self ( Golubickis et al, 2017 ). Moreover, the self-reference effect has been observed cross-culturally ( Jiang et al, 2019 ), suggesting that the self-bias does not depend on the kind of society one belongs to (such as individualistic society or collective society; however, see Verma et al, 2021 ). For example, Jiang et al (2019) showed a comparable self-advantage in the participants from the UK as well as Hong Kong (HK), suggesting that self-bias could be a universal phenomenon (however, HK participants show similar performance in the friend and stranger category; also see Zhu and Han, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation